Boolean Functions for Stream Ciphers - Potii, Oleksandr; Poluyanenko, Nikolay; Petrenko, Anna; Pidkhomnyi, Oleg; Florov, Serhii; Kuznetsova, Tetiana (2019 IEEE 2nd Ukraine Conference on Electrical and Computer Engineering (UKRCON), 2019)
The possibility of generating a special type of sequence, called de Bruijn sequence, at minimal hardware and software costs to implement nonlinear Boolean functions, and apply them in stream encryption systems, is the main subject of this work. The paper presents the possible structure boundaries (algebraic degree of a Boolean function, the number of monomials in a function) of iterative de Bruijn sequence bitrate generators for various generated sequence characteristics, such as linear complexity and autocorrelation function. The profile of the linear complexity of the studied sequences is closed to the expected value of the linear complexity, as well as for a truly random sequence.